Analysis of tensile failure load of single-lap green composite specimen welded by high-frequency ultrasonic vibration. (2020) - Choudhury, Mridusmita Roy; Debnath, Kishore
Abstract: Ultrasonic welding is a solid-state fusion bonding method which is mostly use to bond thermoplastic parts by means of high-frequency ultrasonic vibration by producing heat at the interface of the joint. It is an eco-friendly, cost-effective, and time-saving method of making joint which requires no additional parts or materials unlike mechanical fastener and bonding materials used in mechanical and adhesive joining. In the present work, high-frequency (20 kHz) ultrasonic vibration was applied to join green composite specimens. The green composite specimens were fabricated using bamboo fiber as reinforcement and poly(lactic) acid (PLA) as a binding polymer. Both these constituents of the composite are biodegradable in nature. The green composites were fabricated by stacking the fiber mats and polymer layer alternatively using hot compression. The overlapping length and the width of the lap-joint specimens were kept constant to 50 and 32 mm, respectively. The strength of the welded lap-joint specimen was evaluated by conducting tensile tests. The influence of the welding parameters such as holding pressure (1, 2, 3, 4, and 5 bar), holding time (1000, 3000, 5000, 7000, and 9000 ms), and welding time (1000, 3000, 5000, 7000, and 9000 ms) on the tensile failure load of the welded specimen were studied by varying one factor at a time. The load-displacement behavior and failure mode of the welded specimen under different experimental conditions were also studied to investigate the ultrasonic welding behavior of the developed green composites.